(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
This article aims to contribute to the studies of the queens starting from a relational history that allows approaching a perspective that leaves aside those interpretative models, which place the male as the only actor of power seeking to contribute to the realization of a more complex history and relational; therefore, show the plurality of experiences and experiences that accompany men and women. In this opportunity we will take the figure of María de Portugal, Reina de Castilla to analyze the political context and the construction of feudal power through complex patronage networks and we will use the concept of regality that will allow us to focus on the study of the "power of the queens”; highlighting the exercise of power together (and in relation) to the King.